FORMULATION AND PHYSICAL STABILITY TEST OF NANOEMULGEL CONTAINING Petrosia Sp. ETHANOLIC EXTRACT - Muhammad Hajrul Malaka; Astrid Indalifiany; Sahidin Sahidin; Adryan Fristiohady; Rina Andriani (Jurnal Farmasi Sains dan Praktis, 2021)
Petrosia sp. is one of the sponges from the demospongia class that has biological activity as anti-inflammatory, antimalarial, cytotoxic agent, and can be used in nanoemulgel formulation. Nanoemulsion system is thermodynamically stable and produces globule size that can increase the permeability and diffusibility of Petrosia sp. The presence of gelling agent in the nanoemulgel gives the viscosity and spreadability of Petrosia sp nanoemulsion optimally to increase the effectiveness of the active substances on the skin. This study aims to determine the formulation, characterization, and physical stability of nanoemulgel ethanol extract of sponge Petrosia sp. with carbopol 940 as the gel base. Nanoemulsion characterization included transmittance value, particle size, polydispersity index, and type of emulsion formed. The physical stability test of nanoemulgel included centrifugation and freeze thaw tests with organoleptic, pH, viscosity, and dispersibility evaluation. Nanoemulsion of Petrosia sp ethanolic extract with a composition of 1% VCO, 7% Tween-80, and 2% PEG-400 produced an oil-in-water (O/W) nanoemulsion, transmittance value of 94.84%, droplet size of 23.9 nm and particle size distribution of 0.176. The optimum formula for nanoemulgel is F1 with a nanoemulsion concentration of 75 mL and 25 g of gel base produced a clear and transparent nanoemulgel, semi-solid, soft texture, distinctive aroma, pH value of 5, viscosity of 28,000, dispersibility of 5.7 cm and the shape/color did not change after freeze thaw stability test. Based on the data above, it can be concluded that the F1 nanoemulgel formula with carbopol 940 as the base gel produced an optimal nanoemulgel.